Ethnicity and Conflict: A Theoretical Perspective - Gulshan Majeed (Journal of Political Studies, 2013)
Ethnicity has been the most significant phenomenon of the modern world. Stratification and diversification with variegated dimensions and context is an inbound mechanism of a social fabric of a society and state. Different scholars, intellectuals and men of letters studied the phenomenon of ethnicity in different ways. Some intellectuals call it as a minority, insiders, outsiders, others and nationalities. Ethnicity can be defined as a group of individuals identified on the basis of race, colour, language and territory. These groups have been existing almost in every part of the world. In reality the states are plural societies with many national, sub-national, religious, professional, racial, linguistic and geographic identities. In some states these identities live side by side, while in others they conflict with each other and undermine political edifice of the society. Ethnic identities live peacefully without conflicting with each other until and unless they are triggered to do so. The apparent and pre-dominant cause of conflict among different ethnic identities is politicoeconomic imbalance and these identities, if in conflict have potential to destabilize or disintegrate the political system of any country. There is hard need to initiate various measures, though which will not eliminate the possibilities of ethnic conflicts, but definitely minimize them.